Disability and cognitive impairment in the elderly - Barberger-Gateau, P; Fabrigoule, C (Disability and rehabilitation, 1997)
Disability and cognitive impairment show similar patterns of increasing frequency with ageing. A review of the published literature shows that there is a cross-sectional relationship between cognitive impairment and disability, independent of demographic, medical, and lifestyle factors. Some instrumental activities of daily living (IADL) items appear more specifically related to cognitive impairment, but cognition and functional impairment are distinct concepts requiring separate assessments. Subjects with low cognitive performances are at higher risk of functional impairment in the following years. Cognitive impairment as well as disability increase the risk of death and institutionalization. Preventive strategies could be directed against the risk factors of cognitive impairment and disability, and would aim to delay the onset of dementia. Prevention of disability associated with cognitive impairment needs further assessment in elderly community-dwellers. Further research is needed to better identify the specific areas cognition involved in the disablement process.